2008
DOI: 10.1097/yic.0b013e3282f424c2
|View full text |Cite
|
Sign up to set email alerts
|

Venlafaxine extended release versus citalopram in patients with depression unresponsive to a selective serotonin reuptake inhibitor

Abstract: Findings from the National Institute of Mental Health's Sequenced Treatment Alternatives to Relieve Depression trial indicate that approximately 50% of patients with major depressive disorder do not experience a treatment response after adequate first-line treatment with a selective serotonin reuptake inhibitor (SSRI). This study was designed to test the hypothesis that, after treatment failure with an SSRI, switching to venlafaxine extended release (ER) would offer advantages over switching to another SSRI, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(25 citation statements)
references
References 17 publications
0
25
0
Order By: Relevance
“…After 4 weeks of either paroxetine or venlafaxine, the venlafaxine group demonstrated a remission rate of 37% compared with the remission rate of 18% in the paroxetine group (p = 0.01). The second double-blind study followed 406 patients who failed to respond to ongoing SSRI treatment [37]. Unlike the prior trial, this study demonstrated no advantage of venlafaxine XR with regard to the primary outcome measure, in this case the HDRS-21.…”
Section: Resultsmentioning
confidence: 95%
“…After 4 weeks of either paroxetine or venlafaxine, the venlafaxine group demonstrated a remission rate of 37% compared with the remission rate of 18% in the paroxetine group (p = 0.01). The second double-blind study followed 406 patients who failed to respond to ongoing SSRI treatment [37]. Unlike the prior trial, this study demonstrated no advantage of venlafaxine XR with regard to the primary outcome measure, in this case the HDRS-21.…”
Section: Resultsmentioning
confidence: 95%
“…In four RCTs in SSRI nonresponders, [3,[9][10][11] a significant benefit with regard to response [11] and/or remission [9,11] was shown in pts switched to venlafaxine vs a second SSRI in two trials Overall, venlafaxine appears to be an effective and useful agent after the failure of an SSRI, but whether it is markedly more effective than other options seems doubtful Switching to a newer SNRI Studies are needed to determine the role of newer SNRIs in treatment-resistant MDD, as no available RCTs have investigated switching to newer SNRIs (e.g. duloxetine, desvenlafaxine and milnacipran) in treatment-resistant pts…”
Section: Switch To a Different Antidepressantmentioning
confidence: 99%
“…An example of an equivocal trial would be an active control equivalence trial, or non-inferiority trial, in which a new drug is compared to a known effective drug, in the absence of a placebo control (7)(8)(9). An example of an equivocal trial would be an active control equivalence trial, or non-inferiority trial, in which a new drug is compared to a known effective drug, in the absence of a placebo control (7)(8)(9).…”
Section: Publication Bias and The Evidence Basementioning
confidence: 99%